2020
DOI: 10.3390/v12030354
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiles Associated with Marek’s Disease Virus in Bursa and Spleen Lymphocytes Reveal Contrasting Immune Responses during Early Cytolytic Infection

Abstract: Marek’s disease virus (MDV), an alpha herpes virus, causes a lymphoproliferative state in chickens known as Marek’s disease (MD), resulting in severe monetary losses to the poultry industry. Because lymphocytes of bursa of Fabricius and spleen are prime targets of MDV replication during the early cytolytic phase of infection, the immune response in bursa and spleen should be the foundation of late immunity induced by MDV. However, the mechanism of the MDV-mediated host immune response in lymphocytes in the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Transcriptome profiling has been used to evaluate the host immune response to MDV infection during the early cytolytic phase by analysis of splenic lymphocytes ( 37 ) and was employed in the current study to elucidate why Md5BAC Δ meq Δ pp38 gave superior protection to CVI988/Rispens. Transcriptome profiling was performed during Md5BAC Δ meq Δ pp38 and CVI988/Rispens lytic replication at 5 dpi, using uninfected spleen samples as negative control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptome profiling has been used to evaluate the host immune response to MDV infection during the early cytolytic phase by analysis of splenic lymphocytes ( 37 ) and was employed in the current study to elucidate why Md5BAC Δ meq Δ pp38 gave superior protection to CVI988/Rispens. Transcriptome profiling was performed during Md5BAC Δ meq Δ pp38 and CVI988/Rispens lytic replication at 5 dpi, using uninfected spleen samples as negative control.…”
Section: Resultsmentioning
confidence: 99%
“…The protective mechanism of an MDV vaccine remains to be elucidated, but previous studies have demonstrated that both pathogenic and nonpathogenic strains stimulate differential gene expression in vitro and in vivo ( 37 , 45 ). CVI988/Rispens inoculation caused altered transcriptome profiles in splenic lymphocytes compared with pathogenic virus in the early cytolytic infection phase ( 37 ). Interestingly, Md5BAC Δ meq Δ pp38 was found to confer superior protection to CVI988/Rispens ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL8, a proin ammatory factor, is associated to the incidence and progression of a variety of in ammatory diseases, including proliferation, angiogenic responses, tumour metastasis, and encouraging infected tissue healing [21]. Previous studies showed that IL8L1 has a causal role in establishing acute in ammation; play important role in PPI network; probably associates with vIL8, which recruits T cells to B cells infected with MDV and leads to transduction of viral signal from B to T cells [22]. IL8L1 was enriched in 15.87% (40/252) GO terms, and the rate was high as 86.67% (26/30) in the top 30 GO terms.…”
Section: Discussionmentioning
confidence: 99%
“…MDV infections result in alterations in the infiltration and proliferation of B cells and CD4+ T cells. As main lymphoid organs in chickens, both the spleen and bursa not only support MDV replication, but also play an important role in immune response [ 15 , 22 , 23 ]. Moreover, the spleen mainly contains B and T lymphocytes, which are dominant target cells of MDV.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study reported that MDV/CVI988 and MDV/RB1B (a vvMDV strain) elicited different host immune responses in early cytolytic infection phase (5 dpi) in vivo experiments. In particular, the transcription level of some cytokines in the splenic lymphocytes, including IL-1β, IL-6, IL-8L1, and CCL4, which are related to B cell activation and antigenic signal transduction to T cells, were significantly upregulated by MDV/CVI988 infection compared with MDV/RB1B infection [ 15 ]. Considering the different pathological responses of the host after infection with the MDV vaccine strain and virulent strain, we speculate that the replication and immune activation status of MDV with different virulence levels also differ during the latent infection and reactivation phases.…”
Section: Introductionmentioning
confidence: 99%